DEVELOPING OF ENGLISH LANGUAGE PRINTED MATERIAL BASED ON 2013 CURRICULUM: ON GIVING EXPRESSION ABOUT CONGRATULATING AND COMPLIMENTING OTHERS - Ija Try Saputri; Kamsinah , (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
The researcher proposed to develop English printed material of Giving Expression about Congratulating and Complimenting others based on 2013 curriculum of the English tenth grade students in SMA Negeri 16 Makassar. According to the interview with one of the English teachers in SMAN 16 Makassar that there are some problems according to the material and layout of the book. In addition, teacher on implementing 2013 curriculum was unprepared and the students faced difficulties in learning English since they didn’t have many references except the students’ book that provided by the government. The research design used in this study was Research and Development (R&D). The development model used was ASSURE model. The instruments used in this study were questionnaire and rubrics for the teacher, students, and experts. In this research, teacher and expert were involved in order to validate the product. There are four aspects that they validated of the product. They are systematic organization of materials, systematic English teaching, systematic content of English, and the language.  To sum-up, the result of this printed material analysis by the expert was well-qualified as on reference used in teaching English material. So, the product was expected to be able to help both the students and teachers in learning and teaching English especially Giving Expression about Congratulating and complimenting others material.